Characterization And Behaviour Of Silicon Dioxide Nanoparticles In Chemical Mechanical Polishing Wastewater With The Presence Of Ferrous Sulphate And Polyaluminium Chloride - Sin, Jing Yao (Universiti Sains Malaysia, 2017)
In the twenty-first century, semiconductor industry is one of the most competitive manufacturing industries around worldwide. This is due to high demand of semiconductor for the manufacturing of electronic devices in this high technology era. While there are many wafers and chips produced daily from the industries, it seems the awareness of people to the environment become lesser among the society. As more semiconductors produced throughout every year, the chemical mechanical polishing (CMP) wastewater generated from the output also increased. In order to prevent the CMP wastewater directly flow into the environment, there are many coagulants and methods done to treat the CMP wastewater. However, the CMP wastewater is always to purify at the best condition as there are some residue in nano-scale still left in the wastewater. In this study, zeta potential and particle size of CMP wastewater are concerned to observe how these characteristics behave along different pH value. The purpose for study of behaviour of zeta potential and particle size is to have a better understanding on the coagulation mechanism. Furthermore, ferrous sulphate and poly-aluminium are used as coagulant in this study to investigate how zeta potential and particle size of CMP wastewater behave as coagulants are added. Based on the results, poly-aluminium is an effective coagulant which able to neutralize the zeta potential of CMP wastewater at 30 mg/L. However, ferrous sulphate does not as much effective as poly-aluminium where zeta potential is slightly lower while particle sizes are remained constant. In conclusion, poly-aluminium has better potential to treat CMP wastewater compare to ferrous sulphate.